Comparative Evaluation of the Effect of Different Universal Adhesives and Bonding Techniques on the Marginal Gap of Class I Composite Restoration (A SEM Study) - Ali F. Al-Qrimli; Abdulla M.W. Al-Shamma (College of Dentistry/ University of Baghdad, 2016)
Background: With the increase in composite material use in posterior teeth, the concerns about the polymerization shrinkage has increased with the concerns about the formation of marginal gaps in the oral cavity environment. New generation of adhesives called universal adhesive have been introduced to the market in order to reduce the technique sensitive bonding procedures to give the advantage of using the bonding system in any etching protocol without compromising the bonding strength. The aim of the study was to study marginal adaptation of two universal adhesives (Single bond™ Universal and Prime and Bond elect) using 3 etching techniques under thermal cycling aging. Materials and Methods: Forty-eight sound maxillary first premolar teeth were included in the study. Teeth were divided into two groups according to the universal adhesive used then each group was subdivided into 3 subgroups according to the etching protocol used. Standardized class I cavities were prepared in the teeth followed by the restoration of teeth using Filtek™ Bulk Fill Posterior Restorative composite material. After finishing and polishing, teeth were subjected to 500 thermal cycles in 55º-5ºC bath with dwell time of 30 seconds. Teeth then were examined using SEM to measure the marginal gap at 12 points. Data obtained were analyzed using one-way ANOVA and LSD test for each group and with student t-test to compare the two adhesives. Results: The result of this study the showed that etch and rinse technique showed significantly the least marginal gap width for both adhesive types. The selective etch technique showed lower gaps compared to the self-etch technique with no significant difference. The result showed that single bond universal showed significantly the least marginal gap for the all etching techniques compared to Prime and bond elect. Conclusion: The etch and rinse technique remains the most suitable technique for adhesive restoration. The type of adhesive plays an important role in adhesion.